Emerging Cutaneous Phaeohyphomycosis Caused by Alternaria infectoria - Kieselová, Katarína (2021)
Alternaria species belong to a group of opportunistic fungi that causes skin infection mainly in immunosuppressed patients. The authors describe two clinically distinct cases of cutaneous alternariosis caused by Alternaria infectoria in patients under prolonged corticosteroid treatment. Additionally, a brief review of published cases in portuguese patients is conducted.